A marca na internacionalização das franquias da América Latina: um estudo de caso das franquias de El Salvador - Andrade, Erick Alejandro Morales de (2020)
This study proposes an analysis of the internationalization process of the Salvadoran franchises. The objective of this work is to investigate the brand influence on the franchising internationalization in the segment of two food and beverage franchises in El Salvador, to verify what decisions were made by the brand managers or CEO regarding the Global Marketing Strategies (GMS). The theoretical background is based on studies about internationalization, seen through the lens of Upsala School, international marketing, and international franchising. The research method was the qualitative, with the development of a multiple case study. We analyzed two Salvadoran franchises that experienced the internationalization process. As a result, the research aims to identify the path that the companies took until the standardization of their mix marketing and the movements that lead their corporate actions to the last four dimensions of the GMS, concentration and coordination of the marketing activities, integration of the competitive movements and global marketing participation. This study innovates by showing the GMS strategies in the context of a country whose market presents different socioeconomic, cultural and behavioral realities within the internationalization process. The contribution of this study is its originality that involves themes such as: the brand, internationalization and international franchising. We realized that the Salvadoran franchises need to be consolidated in Latin America, to have a more remarkable recognition and to apply marketing strategies aimed at the international markets